Numerical investigation of the effect of triangle strut in vertical axis wind turbine (VAWT) - Tri Admono; Yoyon Ahmudiarto; Amma Muliya Romadoni; Iman Abdurahman; Agus Salim; Teguh Tri Lusijarto; Mochammad Agoes Mulyadi (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2020)
Strut is used in vertical axis wind turbine (VAWT) to restraint the framework. In this study, struts are analyzed to show the pressure losses in VAWT. ANSYS computational fluid dynamics (CFD) software is used to investigate triangle strut in VAWT. This study aims to show a CFD simulation of struts, which affects the aerodynamic of VAWT. In CFD software, the aerodynamic of VAWT can be analyzed in terms of pressure losses in the struts. The simulation method starts by making a struts model, then meshing and setting up ANSYS's boundary conditions. The last iteration runs in ANSYS until convergence. Our results show the percentage of pressure losses with the variation of the angle of wind 0°, 20°, 40°, and 60° are 0.67 %, 0.52 %, 0.48 %, and 0.52 %. The effect of triangle strut in VAWT did not affect the wind flow to the VAWT blade. The results also indicated that the triangle strut could be applied in the multi-stage of VAWT system.